Contested Spaces: Entanglement of Chinese Migration, Gender Discrimination, and Colonial Resistance in Olivia Ho’s “Working Woman” - Boy Ertanto (Journal of Language and Literature, 2022)
Southeast Asian colonial experiences are of immense significance yet under-exposed. It entails an irony as Southeast Asia as a geographical entity is one of the most colonized regions in the history of humankind. This paper serves to provide an elaboration of the Chinese Singaporean colonial experiences during the British occupation in Singapore in a steampunk short story entitled “Working Woman” by Olivia Ho. This short story is compiled in an anthology of Southeast Asian steampunk short stories named The Sea is Ours: Tales from Steampunk Southeast Asia edited by Jaymee Goh and Joyce Chng. Postcolonial feminism approach is utilized as the critical framework in the analysis of the story. The analysis finds that there are three contesting themes in the narrative namely 1) the reception of forced migration of the Chinese that result in their permanent residence in Singapore, 2) double colonization undergone by the Chinese female characters, and 3) the resistance toward British colonial power and patriarchal subjugation in the Singaporean Chinese society. The three themes intermingle as a linear course of history rather than an independent sub-historical phenomenon within the fiction. Thus, the reception of Chinese migration in the fiction is made possible by the arrival of British colonialism in Singapore and as a result, discrimination and resistance of Chinese women become the implication of the contact of colonialism and migration.